Numerical Analysis on Flexural Behaviors of Prestressed Reinforced Concrete Beams Strengthened with NSM CFRP Strips - Jia Yang; Xiao Liu; Wei Li (Advances in Materials Science and Engineering)
This paper presents the numerical analysis of prestressed reinforced concrete (PRC) beams strengthened with near-surface mounted (NSM) carbon fiber reinforced polymers (CFRP). ABAQUS finite element software was used to simulate the existing test beams to investigate the flexural behaviors of PRC beams strengthened with NSM CFRP strips. The finite element model of beams strengthened with NSM CFRP strips was established. The finite element calculation results were compared with the experimental results to verify the accuracy and effectiveness of the model. Based on this model, the influences of concrete strength grade and amount of CFRP strips on the flexural behaviors of directly strengthened beams and the cycle numbers and overload amplitude on the flexural behaviors of damaged strengthened beam were further analyzed, and the load-carrying capacity calculation formula of PRC beam strengthened with NSM CFRP strips was established. The results showed that the simulation results and the theoretical calculation were consistent with the test results. With the increase of concrete strength grade and amount of CFRP strips, the ultimate load of directly strengthened beams increased significantly, with a maximum increase of 21.3% and 23.0%, respectively. When the concrete strength grade exceeded C50, the improvement of the ultimate load was limited. When the overload amplitude was less than 60% of the ultimate load, the cycle numbers (within 500 times) had little effect on the yield load, ultimate load, and deformation. When the overload amplitude was higher than 60% of the ultimate load, the deformation increased, and the ultimate load decreased with the increase of the cycle numbers. The larger the overload amplitude, the smaller the ultimate load, and the larger the deformation under the same cycle numbers.